Phenylalanine Blocks Defects Induced in Gel Lipid Membranes by Osmotic Stress - Cutró, Andrea Carmen (2015)
We study the binding of phenylalanine (Phe) with dipalmitoylphosphocholine (DPPC) vesicles in gel (25°C) and in liquid crystalline states (50°C) and in gel large unilamellar vesicles (LUVs) subjected to osmotic dehydration with merocyanine (MC 540) as a fluorescent surface membrane marker. Phe does not produce significant changes in MC 540 monomer concentration in DPPC LUVs at 50°C. In contrast, it significantly decreases the monomer adsorption in defects present in DPPC LUVs at 25°C. When DPPC LUVs were subjected to hypertonic stress, dehydration caused more defects, and in this case phenylalanine is also able to block such defects.